Firm-level participative leadership and individual-level employee ambidexterity: A multilevel moderated mediation analysis. Issue 5 (24th July 2019) - Chang, Yi-Ying; Chang, Che-Yuan; Chen, Chung-Wen; Chen, Y.C.K.; Chang, Shu-Ying
Abstract : Purpose: The purpose of this paper is to examine if personal identification could explicate the black box between participative leadership and employee ambidexterity. Also, the authors aim to explore how and why the top-down effects of higher-level leadership styles affect lower-level outcomes. Design/methodology/approach: The authors collected multilevel and multisource data from top manager teams, and unit managers and employees of research and development, marketing and sales, and operations from Taiwanese technology firms. Findings: The results revealed that individual-level personal identification partially mediated the relationship between firm-level participative leadership and individual-level employee ambidexterity, and individual-level coworker social support moderated the effect of firm-level participative leadership on individual-level employee ambidexterity through individual-level personal identification. Originality/value: This paper demonstrated the importance of participative leadership and personal identification. It contributed to profound comprehension for potential mechanisms of individual-level personal identification and an enhancer of individual-level coworker social support why and how affects firm-level participative leadership on individual-level employee ambidexterity.